Predicting bootcamp success - Santos, Ricardo (2024)
Santos, R., Pesovski, I., Henriques, R., & Trajkovik, V. (2024). Predicting bootcamp success: using regression to leverage preparatory course data for tech career transitions. In L. G. Chova, C. G. Martínez, & J. Lees (Eds.), 16th International Conference on Education and New Learning Technologies 1-3 July, 2024 Palma, Spain (pp. 6181-6190). (EDULEARN24 Proceedings; No. 2024). IATED Academy. https://doi.org/10.21125/edulearn.2024.1465